Innovation in Urology: Three Dimensional Printing and Its Clinical Application - Mathews, David A. P.; Baird, Andrew; Lucky, Marc (Frontiers in Surgery, 2020)
Three-dimensional (3D) printing allows rapid prototyping of novel equipment as well as the translation of medical imaging into tangible replicas of patient-specific anatomy. The technology has emerged as a versatile medium for innovation in medicine but with ever-expanding potential uses, does 3D printing represent a valuable adjunct to urological practice? We present a concise systematic review of articles on 3D printing within urology, outlining proposed benefits and the limitations in evidence supporting its utility. We review publications prior to December 2019 using guidelines outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. Of 117 identified articles, 67 are included highlighting key areas of research as the use of patient-specific models for patient education, surgical planning, and surgical training. Further novel applications included printed surgical tools, patient-specific surgical guides, and bioprinting of graft tissues. We conclude to justify its adoption within standard practice, further research is required demonstrating that use of 3D printing can produce; direct and measurable improvements in patient experience, consistent evidence of superior surgical outcomes or simulation which surpasses existing means' both in fidelity and enhancement of surgical skills. Although exploration of 3D printing's urological applications remains nascent, the seemingly limitless scope for innovation and collaborative design afforded by the technology presents undeniable value as a resource and assures a place at the forefront of future advances.